A case report of synchronous triple primary malignancies: Diffuse large B-cell lymphoma, rectal adenocarcinoma and hepatocellular carcinoma - Qiu, Beixuan; Lin, Cheng; Wu, Lupeng; Li, Yifei (Frontiers in Oncology, 2022)
A 59-year-old man was admitted to our hospital in August 2020 because of fever with night sweats and weight loss. The patient was eventually diagnosed with synchronous triple primary malignancies: diffuse large B-cell lymphoma (DLBCL), rectal adenocarcinoma and hepatocellular carcinoma (HCC), which has not been reported previously. The patient initially received six cycles of R-Gemox chemotherapy targeting DLBCL, the response to the treatment was partial remission. We continued six cycles of R-CHOP therapy, and DLBCL achieved a complete remission to treatment. During R-CHOP chemotherapy, PD-1 inhibitor (Sintilimab) was used to control the disease progression of HCC, which was effective and tolerable. Subsequently, he successfully completed curative intent Dixon operation and right hemihepatectomy. The diagnosis and treatment for like this synchronous triple primary malignancies are a huge challenge, herein we provide our experience in this regard.